Seedlings formation of coffee clonal influenced by cuts basal and substrate - de Aquino, Lourena Pegorer; Schmidt, Raquel; Dubberstein, Danielly; Machada Dias, Jairo Rafael (Coffee Science - ISSN 1984-3909, 2017)
This study aimed to evaluate substrates and types of basal cuts on stakes for the production of coffee clonal seedlings. The experiment was carried out in a greenhouse. The cuttings were obtained from the middle portion of standardized orthotropic branches. The experiment was a factorial 2x7 with two types of cuttings (basal cut straight and bevel) and seven substrates: soil, commercial, coffee straw, wood shavings (processed wood waste), commercial + coffee straw (v: v) , commercial + shavings (v: v), straw coffee + wood shavings (v: v). It was verified that the commercial substrate Vivato Slim when using or not coffee straw, and the basal rectilinear cutting in Coffea canephora stakes have better results for the production of clonal seedlings under the conditions investigated in this work.